Folklore and Sociolinguistics - John Holmes, McDowell (MDPI AG, 2018)
Folklore and sociolinguistics exist in a symbiotic relationship; more than that, at points—in the ethnography of communication and in ethnopoetics, for example—they overlap and become indistinguishable. As part of a reaction to the formal rigor and social detachment of Chomsky’s theoretical linguistics, sociolinguistics emerges in the mid-twentieth century to assess the role of language in social life. Folklorists join the cause and bring to it a commitment to in-depth ethnography and a longstanding engagement with artistic communication. In this essay, I trace key phases in the development of this interdisciplinary movement, revolutionary in its reorientation of language study to the messy but fascinating realm of speech usage. I offer the concept of performative efficacy, the notion that expressive culture performances have the capacity to shape attitude and action and thereby transform perceived realities, as a means of capturing the continuing promise of a sociolinguistically informed folkloristics.